Sales scripts that sell - Gamble, Teri Kwal (AMACOM/American Management Association, 2007)
"Completely updated with new material, Sales Scripts That Sell is designed to give you a real selling advantage over your competition. Whether you are a novice or a seasoned professional, this invaluable guide provides you with the language and tips you need to talk your way to success. Authors Teri and Michael Gamble have spent years showing clients how to prepare for just about any selling situation. With their fool-proof, proven advice, you can avoid the costly sales mistakes, rejections, turn-downs, and stalls that can impede any closing. An all-in-one training manual for every level of experience, this book will show you how to master the complete sales process."--Jacket